Slowing the spread: assessing early Covid-19 intervention effectiveness in São Paulo using socio-demographic and mobility data - Yucel, S (2021)
Background and Motivation: The COVID-19 pandemic continues to have devastating health, social, and economic impacts around the world. Brazil ranks second globally in COVID-19 deaths, with spiraling growth after its first case in the Metropolitan Region of S ̃ao Paulo (MRSP), the largest urban agglomeration in South America. Lockdown interventions to reduce mobility are a leading tool for infection mitigation, and while effective on aggregate, their adherence is impacted by socio-demographic factors. A forward-looking model that evaluates the ability of lockdowns to slow disease spread through a socio-demographic lens can inform more equitable policy-making.